Soil organic matter and water content affect the community characteristics of arbuscular mycorrhizal fungi in Helan mountain, an arid desert grassland area in China - Shao, Leilei; Yan, Peixuan; Ye, Siqi; Bai, Hao; Zhang, Rui; Shi, Guangyao; Hu, Yang; Pang, Danbo; Niu, Xiang; Ni, Xilu (Frontiers in Microbiology, 2024)
Arbuscular mycorrhizal fungi (AMF) play a vital role in terrestrial ecosystems.However, the community structure characteristics and influencing factors of AMF in the forest ecosystems of arid desert grassland areas require further investigation. Therefore, we employed high-throughput sequencing technology to analyze the soil AMF community characteristics at different elevations in the Helan Mountains. Our study aimed to explore the relationship between AMF community structure and environmental factors. The primary findings are as follows: (1) Significant differences (P<0.05) were observed in the soil physicochemical properties among different elevations, and these properties exhibited distinct trends with increasing elevation. (2) Through high-throughput sequencing, we identified a total of 986 operational taxonomic units (OUTs) belonging to 1 phylum, 4 classes, 6 orders, 12 families, 14 genera, and 114 species. The dominant genus was Glomus. Furthermore, significant differences (P<0.05) were observed in the αdiversity of the soil AMF community across different elevations. (3) Person correlation analysis, redundancy analysis (RDA), and Monte Carlo tests demonstrated significant correlations between the diversity and abundance of AMF communities with soil organic matter (OM) (P<0.01) and soil water content (WC) (P<0.05). This study provides insights into the structural characteristics of soil AMF communities at various altitudes on the eastern slope of Helan mountain and their relationships with soil physicochemical properties. The findings contribute to our understanding of the distribution pattern of soil AMF and its associations with environmental factors in the Helan Mountains, as well as the stability of forest ecosystems in arid desert grassland areas.